Archaeology on the Threshold Studies in the Processes of Change. - Wardle, Joseph D. (University Press of Florida, 2022)
Incorporating data from across six continents and tracingthe human experience from the Late Pleistocene to the present, this volumeexamines transitional periods of cultural and environmental changethrough the lenses of archaeology and ethnography.